Can Liquidity, Profitability, and Leverage Predict Financial Distress? - Oktrivina, Amelia; Heriansyah, Kurnia; Fryenddisca, Fiona Almyra (SAN Scientific, 2025)
This study analyzes the influence of liquidity, profitability, and leverage on financial distress among manufacturing firms in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) during 2019–2022. Using purposive sampling, 48 firms were selected, producing 192 observations. The results show that liquidity and leverage do not significantly affect financial distress, while profitability has a significant impact. These findings underscore the crucial role of profitability in maintaining financial stability. Managerially, firms should prioritize profitability improvement through operational efficiency, cost control, and revenue diversification to avoid financial distress, especially during economic downturns. Although liquidity and leverage were not significant, maintaining prudent management of both remains essential for long-term resilience. This study’s originality lies in examining the combined effects of liquidity, profitability, and leverage in Indonesia’s post-pandemic basic and chemical manufacturing sectors, using logistic regression as a predictive tool. In contrast to prior research conducted before crises or using single-variable approaches, this study provides new empirical evidence that profitability serves as the key determinant of financial distress under unstable macroeconomic conditions, offering valuable insights for both researchers and industry practitioners.